Analysis of factors affecting poverty in Java Island - Nunung Robiatul Rifkah; Rifda Nabila (Indonesian Journal of Islamic Economics Research, 2021)
This study aimed to determine the effect of the Human Development Index, GRDP, and unemployment by utilizing zakat as a moderator on poverty in Java in 2014-2019. This study used secondary data with a panel data model, namely annual data from six provinces in Java. The analysis method used is multiple linear regression analysis with the Moderated Regression Analysis (MRA) test. The research results showed that the Human Development Index has a significant negative effect on poverty, GRDP has a negative and insignificant effect on poverty, unemployment has a negative and insignificant effect on poverty. The Moderated Regression Analysis (MRA) test shows that zakat cannot moderate the relationship between the human development index, GRDP, and unemployment on poverty.